Optimalisasi Penerapan Authentic Assesment dalam Pembelajaran Bahasa Inggris di SMP-IT Al-Izhar Kota Pekanbaru - Roswati Roswati; Nurdiana Nurdiana; Fatimah Depi Susanty; Zikri Rahman (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2019)
This study aims to find out and describe the optimization of the application of authentic assessment and the factors that influence the application of authentic assessment in learning English in Al-Izhar Junior High School, Pekanbaru. The research method used in this research is a qualitative method with an inductive descriptive approach. With the method of data collection using observation, interviews and documentation. The results of this study are in optimizing the application of authentic English learning assessment in Al-Izhar SMP-IT Pekanbaru City, researchers conclude that the English language teacher at Al-Izhar Pekanbaru IT Middle School has conducted an authentic assessment and needs to be improved again because there are still indicators that have not been implemented. The researcher's findings are that the teacher has: 1) measured all aspects of learning, namely performance and results or products, 2) conducted an assessment during the learning process until learning was completed, 3) used a verbal and written assessment in the form of vocabulary pronunciation and mastery of students' English vocabulary and writing, 4) using oral exams and written tests and not just based on tests, 5) giving assignments that reflect daily life and recounting experiences or activities on a daily basis, 6) emphasizing product quality or performance rather than single answers, 7) conduct in-depth assessments, 8) focus on developing students 'English proficiency, 9) develop mastery of learning material, 10) subject teachers in assessing students' emphasis on listening practice, listening skills, speaking , reading (reading) reading ) and writing ( writing ); and 11) instruments in the form of tests and non-tests. There are supporting factors and inhibiting factors, research findings on supporting factors in SMP-IT. Al-Izhar Pekanbaru City, namely: (1) the competency of the teacher, (2) the readiness of the students, (3) the principal's leadership pattern, (4) the realization of a conducive learning environment, and (5) the existence of extra-curricular activities. The inhibiting factors encountered by English subject teachers in applying authentic assessment are: a) the lack of socialization about the 2013 curriculum, because authentic assessment is basically a necessity in the 2013 curriculum; b) the assessment of attitudes in English subjects does not cover the whole assessment of attitudes that are not like the subjects of citizenship education and Islamic Religious Education.